(untitled) (Proceedings of International Educators Conference, 2024)
This article addresses the crucial need for enhancing financial control and internal audit services within budget organizations, which are responsible for managing public funds effectively. The focus on improvement is driven by the increasing demand for transparency, accountability, and efficiency in public financial management. Developing and reinforcing systems that allow for better monitoring of financial activities, ensuring compliance with financial regulations, and preventing fraudulent practices. Improving the methodologies and effectiveness of internal audits to provide comprehensive evaluations of risk management and financial reporting processes. This includes adopting best practices and standardizing audit procedures. Implementing modern technologies such as data analytics and automated financial systems to streamline processes, improve accuracy in reporting, and facilitate real-time monitoring of financial activities.